Study of knowledge, perception, and practice of patients regarding fasting requirements for blood glucose testing - Dr. Asmita Hazra; Dr. Saptarshi Mandal; Dr. Seema L. Jawalekar; Dr. Jairam Rawtani; Ms. Minal Marlecha (International Journal of Medical Research and Review, 2021)
Background: Patient preparation is one of the least standardized parts of the preanalytic phase of testing. Fasting blood glucose requires fasting for 8-12 hours as per various guidelines and also has several other requirements. Lack of communication, understanding, or compliance regarding hours-of-fasting, water-intake, avoidance of caloric snack/beverage, the sudden change in smoking, exercise, alcohol, medication, etc. introduces preanalytic errors. Method: To evaluate awareness, understanding, and compliance with fasting requirements, a face-to-face survey was done on outpatients in a Government Hospital in Pali, Rajasthan, India. Relatively more educated internet users were surveyed as controls through an online SurveyMonkey tool. Information collected included demographics, perception of above mentioned preanalytic factors related to fasting, and compliance. Results: 98 patients and 187 controls participated in the study. Perception about fasting requirements ranged from 0-17 hours. 71% of patients and 35% of controls perceived that nobody explained to them the duration or nature of fasting. The different sources of information had been used in different proportions by patients and controls. For imparting understanding and compliance about duration, and other requirements of fasting, the instruction was usually incomplete but still much more effective (p-value=0.000002) than formal education level (p-value=0.024). Financial status had a weak negative association with awareness but was not significant. Conclusion: 71% of patients and 35% of controls did not receive instructions for fasting. 40% of those instructed showed better compliance, but awareness was incomplete. The instruction was more effective than formal education in improving awareness and compliance. Improved awareness was strongly associated with receiving instruction and weakly associated with formal education but financial status showed only a weak negative association.